Functionality of the modules of the educational program “ERDAS IMAGINE” - Balanbaev Даулет (Рroblems of engineering and professional education, 2023)
ERDAS IMAGINE, now, is the most developed commercial products for the treatment of remote sensing, accessible to a wide range of users. A wide range of tools allows you to analyze data from any source and present information in different formats, from digital maps to 3D- models. ERDAS IMAGINE is created by modular-hierarchical principle. ERDAS IMAGINE features may vary depending on the user’s needs when creating geospatial projects of IMAGINE Essentials, through IMAGINE Advantage, to IMAGINE Professional. To improve performance and increase the capabilities of remote sensing data processing additional specialized modules available